ANALISIS KETAHANAN FATIGUE PADA HEX SOCKET HEAD BOLT A325 DENGAN ULIR DAN TANPA ULIR - Muhammad Hilmi Aziz (Jurusan Teknik Mesin, 2022)
This research was conducted at the LAB of the Faculty of Engineering, University of Jember from September 2020 to July 2021. This study used Ansys Student 19.1 Software and analytical calculations of fatigue life. Data retrieval is carried out on bolts hex socket head bolt with and without thread This research was conducted under static conditions. bolt hex socket head bolt has a size with a length of p = 70 mm, thread diameter = 12 mm. Material bolts using ASTM A325 steel. The results of this study include, stress, fatigue life, fatigue damage and safety factor. From the results of the study, it can be concluded that the results of the comparison between simulation and analysis in table 4.4 have a significantly greater comparison between fatigue life and fatigue damage namely 62.73% and 99.76%, respectively. While in table 4.5 the comparison is significantly greater in the fatigue damage and safety factor , namely 89.97% and 54.59%, respectively. In the comparison results, it still exceeds the errorassumptions cycle bolt hex socket head